2017
DOI: 10.1177/0194599817696302
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Relationship between the Location of the Anterior Ethmoid Artery and Keros Classification

Abstract: Objective We sought to identify a relationship between skull base height and anterior ethmoid artery (AEA) anatomy. Study Design Retrospective radiologic chart review. Setting University of Arkansas for Medical Sciences. Subjects Patients seen in a tertiary rhinology clinic between September 2014 and October 2015. Methods Review of 101 maxillofacial computed tomography scans with institutional review board approval. Skull base height and AEA locations were measured on each side. Prevalence of the AEA outside o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
3
16
2
9
Order By: Relevance
“…Our study confirms the findings by Poteet et al . that higher Keros classification is associated with AEA emerging below the level of the skull base.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study confirms the findings by Poteet et al . that higher Keros classification is associated with AEA emerging below the level of the skull base.…”
Section: Discussionsupporting
confidence: 93%
“…found the AEA to be located below the skull base in approximately 12.5% of the nasal cavities studied. Recently, Poteet et al . further described the position of the AEA with respect to the skull base in a retrospective CT study of 101 maxillofacial scans; they found that the AEA was located below the skull base in 25.7% of cases and more often in Keros type 3 than Keros type 1 or type 2 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean distance between the AEA and the skull base in the current study was 1.37 AE 1.98 mm (range: 0-8.35 mm) that is near to mean distance measured by Ko et al study 39 (1.65 AE 1.9, with range: 0-6.7 mm). On the other hand, Simmen et al 7 and Poteet et al 38 found that the artery was lying 3.7 mm (range: 1-8 mm) away from the skull base.…”
Section: Discussionmentioning
confidence: 95%